Dilemma Between Density and Quality: The demographic history of Sinan Road area - Zhu, Kaiyi (International Planning History Society Proceedings, 2018)
This paper investigates the unique urban planning history and demographic changes in Sinan Road (also named as Rue Massenet) Area of Shanghai and the socioeconomic impacts on local inhabitants’ living quality led by formal and informal planning dynamics. Examining both tangible and intangible characteristics of this area under five different historical phases, this paper indicates that population density and urban quality cannot always be positively or negatively related. Urban quality can reach the maximum value when area population of concentrated density stays in an ideal state, although, as a result of the qualitative variates, such state (peak value) is in suspense. Through analysing the overarching strategic plan of different periods, it also argues that urban quality is not merely dominated by or directly related to density but more by the population’s social demands and their initial interaction with a specific area, active or passive involvement.